A high-performance dual-ion cell utilizing Si nanosphere@graphene anode. (20th August 2018) - Wang, Shuai; Xiao, Xiang; Zhou, Yanping; Fu, Chaopeng; Jiao, Shuqiang
Abstract: The growing global demands of high-safety, low-cost and high working voltage energy storage devices trigger great interests in novel batteries beyond state-of-the-art lithium-ion battery. Herein, we firstly fabricate a novel rechargeable dual-ion cell with graphite cathode and Si nanosphere@graphene (Si-NS@G) composite anode in a LiPF6 -based organic electrolyte. The graphene layers anchored onto Si nanospheres surface can accommodate the volume expansion and improve the electrical conductivity of Si nanospheres. The cell shows stable long-term cycling and excellent rate performance with a high discharge capacity of 100 mA h g −1 at the current density of 100 mA g −1 after 1000 cycles. Moreover, the cell operates a high working voltage of >4.2 V, enabling a higher energy density. Our result may open a new paradigm for novel electrochemical cell technologies and applications. Graphical abstract: Image 1